Administrative Controls and Performance of County Governments in Kenya - Muriithi, Peter Moffat; Kariuki, Paul; Deya, Jared; Kimani, Ezekiah (Human Resource and Leadership Journal, 2026)
Purpose: The devolved units of the county governments in Kenya are intended to play a key part in the country's growth through providing public services. The Kenyan County administrations especially the devolved units have been plagued by a slew of issues, including sloppy work, low-quality goods and services, inefficiency, corruption and lack of professionalism leading to waste of huge amounts of public resources. The devolved unit’s administrative governance structures in Kenya still find it hard to effectively and efficiently deliver services to citizen. The general objective of the study is to examine the influence of administrative controls on performance of county governments in Kenya. Theory that guided the study was Development Administration Theory (DAT). Methodology: The study employed a descriptive research design that also employs the quantitative and qualitative approaches due to its in-depth analysis of the influence of administrative governance structures on service delivery in the devolved units in selected county governments in Kenya. The study targeted all the 47 county governments in Kenya. In this study, the unit of analysis was 47 county governments while the unit of observation comprised of 10 County executive committee’s members (CECs) in each county thus making 470 and 47 speakers of the county assemblies hence making a total of 517 respondents. The study’s sample size was reached at using Krejcie and Morgan sample size determination formula. The 220 respondents were chosen with the help of stratified random sampling technique. Structured questionnaires and interview schedule was used in the collection of qualitative and quantitative data. The data collection tools were pilot tested to confirm their reliability and validity. Findings: The study found that administrative controls positively and significantly influence performance of county governments in Kenya. from citizens, civil society organizations, and experts. Unique Contribution to Theory, Practice and Policy: The study recommends that the management of county governments in Kenya should strengthen internal auditing and oversight mechanisms within county departments. This can be achieved by establishing independent audit units with the authority to regularly review and assess the efficiency, effectiveness, and compliance of administrative processes